2017
DOI: 10.1097/aud.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Visual Temporal Acuity Is Related to Auditory Speech Perception Abilities in Cochlear Implant Users

Abstract: Objective Despite significant improvements in speech perception abilities following cochlear implantation, many pre-lingually deafened cochlear implant (CI) recipients continue to rely heavily on visual information to develop speech and language. Increased reliance on visual cues for understanding spoken language could lead to the development of unique audiovisual integration and visual-only processing abilities in these individuals. Brain imaging studies have demonstrated that good CI performers, as indexed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Nonetheless, as long as they occur within a short period of time, referred to as the temporal binding window (TBW), they are interpreted as a unified percept. Previous work has demonstrated that people with certain diagnoses, such as dyslexia, autism, and schizophrenia, tend to have widened audiovisual TBWs compared with normal controls (Jahn et al 2017;Martin et al 2013;Stevenson et al 2014;Wallace and Stevenson 2014). Wide TBWs may cause individuals with these diagnoses to merge unrelated stimuli into a single, unified percept, leading to sensory confusion and perhaps explaining some of the characteristics of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, as long as they occur within a short period of time, referred to as the temporal binding window (TBW), they are interpreted as a unified percept. Previous work has demonstrated that people with certain diagnoses, such as dyslexia, autism, and schizophrenia, tend to have widened audiovisual TBWs compared with normal controls (Jahn et al 2017;Martin et al 2013;Stevenson et al 2014;Wallace and Stevenson 2014). Wide TBWs may cause individuals with these diagnoses to merge unrelated stimuli into a single, unified percept, leading to sensory confusion and perhaps explaining some of the characteristics of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, group differences were only evident when age was included as a covariate in the comparison to correct for the fact that the CI group was older by 8.4 years (Table 2 ). A preliminary study from our group also suggests that visual temporal thresholds in prelingually deafened adults with CIs are predictive of speech comprehension 54 . In the future, closer age-matching between groups, particularly with the vTOJ task, will better eliminate this potential confound and allow us to further investigate between-group differences.…”
Section: Discussionmentioning
confidence: 71%
“…Given this, temporal processing across sensory modalities is vital for efficient and effective multisensory integration. Indeed, it is common for clinical populations that exhibit deficits in multisensory temporal processing to concurrently exhibit deficits in integration (Baum et al 2015a, 2015b; Bebko et al 2006; de Boer-Schellekens et al 2013; Fister et al 2016; Hairston et al 2005; Noel et al, In Press; Stevenson et al In Press; Stevenson et al 2015; Stevenson et al 2014b; Stevenson et al 2014c; Wallace et al 2014; Woynaroski et al 2013). Simultaneity judgment tasks are one of the most common paradigms for measuring multisensory temporal perception.…”
Section: Low-level Non-speech Sensory Processing With Cismentioning
confidence: 99%
“…the more precise their temporal perception), the better their performance in an audiovisual speech-in-noise task (Baskent et al 2011). Furthermore, recent evidence suggests that visual temporal acuity is predictive of auditory word and sentence recognition in CI users (Jahn et al In Press). …”
Section: Low-level Non-speech Sensory Processing With Cismentioning
confidence: 99%